2017
DOI: 10.1353/hpu.2017.0063
|View full text |Cite
|
Sign up to set email alerts
|

Effective Strategies for Affordable Care Act Enrollment in Immigrant-Serving Safety Net Clinics in New Mexico

Abstract: In the new Affordable Care Act (ACA) health care environment, safety-net institutions continue to serve as important sources of culturally appropriate care for different groups of immigrant patients. This article reports on a qualitative study examining the early ACA enrollment experiences of a range of health care providers (n = 29) in six immigrant-serving safety-net clinics in New Mexico. The six clinics configured their ACA enrollment strategies differently with regard to operations, staffing, and outreach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…One rural system along the U.S.-Mexico border reconfigured the work roles of their three long-term CHWs. The CHWs were bilingual community residents who had already cultivated trust with patients through their work on other projects; leveraging this established trust was essential for enrolling high numbers of long-term LPRs who had newly become eligible for Medicaid (Getrich et al 2017). CHWs have been demonstrated to be an especially important resource for immigrants and their children in navigating complicated eligibility and benefits policies (Cacari Stone et al 2014).…”
Section: Results: Aca Implementation Experiences In New Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…One rural system along the U.S.-Mexico border reconfigured the work roles of their three long-term CHWs. The CHWs were bilingual community residents who had already cultivated trust with patients through their work on other projects; leveraging this established trust was essential for enrolling high numbers of long-term LPRs who had newly become eligible for Medicaid (Getrich et al 2017). CHWs have been demonstrated to be an especially important resource for immigrants and their children in navigating complicated eligibility and benefits policies (Cacari Stone et al 2014).…”
Section: Results: Aca Implementation Experiences In New Mexicomentioning
confidence: 99%
“…Clinic systems configured their ACA enrollment strategies differently (Getrich et al. ). On one end of the spectrum, an urban AHC outpatient clinic retained the same basic clinic setup, with no additional personnel added for the ACA ramp‐up, let alone specifically tailored to the needs of their majority immigrant patients.…”
Section: Results: Aca Implementation Experiences In New Mexicomentioning
confidence: 99%
“…Other studies support these emerging barriers. For example, Medicaid expansion from the ACA covered fewer services than those provided by regular Medicaid (Joseph & Marrow, 2017) and safety-net providers had "no brochures or informational workshops" on how to help their patients enroll in the ACA (Getrich et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies identified [16][17][18][19][20][21][22] individual assistance as a key strategy used by healthcare providers and community-based organizations to help people enroll for health insurance. The terminology used to describe individual assistance varied.…”
Section: Individual Assistancementioning
confidence: 99%
“…Some assisters working for Federally Qualified Health Centers (FQHCs) and communitybased clinics (non-FQHC clinics) also engaged in community outreach. These outreach events included health education workshops and other face-to-face interactive events that enabled them to disseminate information about health insurance and enrolling for coverage [17]. Some FQHCs and community-based organizations had assistance programs prior to the implementation of the ACA.…”
Section: Individual Assistancementioning
confidence: 99%